THE ORGANIZATION AND IMPLEMENTATION OF THE PROFESSION-ORIENTED ENGLISH WRITING EXPERIMENTAL TRAINING OF FUTURE SPECIALISTS IN PUBLISHING INDUSTRY - Антоненко, І. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article is devoted to the problem of teaching foreign languages in non-linguistic universities. The article focuses on the organization and implementation of the profession-oriented English writing experimental teaching to the future specialists of publishing sphere. Certain attention is paid to the development of professionally oriented written communication in a foreign language and training specialists who can effectively use knowledge of the English language in professional sphere. The aim of this experimental study is to test the efficiency of the developed technique for formation of English language competence in writing informational and advertising messages by future professionals of the publishing industry. The genre approach provides the ability to simulate situations of professional communication and to use professional texts, which promotes the development of genre competence of specialists